Vitrectomy with Fovea Sparing Internal Limiting Membrane Peeling versus Total Internal Limiting Membrane Peeling for Myopic Traction Maculopathy - Mahmoud Ali (Al-Azhar University, Faculty of Medicine (Damietta), 2021)
Background: Myopic traction maculopathy [MTM] complicating high myopia is a spectrum of diseases involving damage of the macula resulting from traction leading to inner or outer retinoschisis, macular detachment, lamellar macular hole, full-thickness macular hole [FTMH] or even retinal detachment.Aim of the work: To compare the role of vitrectomy with total internal limiting membrane peeling [TILMP] versus fovea sparing internal limiting membrane peeling [FSILMP] for MTM.Patients and Methods: The study was conducted on eighteen eyes with MTM. Preoperatively, best corrected visual acuity [BCVA] converted into logMAR and optical coherence tomography [OCT] were done. Nine patients were surgically treated with total ILM peeling and nine patients were surgically treated with fovea sparing ILM peeling. Six months postoperatively, the patients were examined for BCVA in logMAR. Also, OCT was done 6 months postoperatively.Results: The difference between the two groups was no significant statistically according to their BCVA preoperatively and postoperatively with a p-value >0.05 NS, while there was a statistically significant reduction BCVA postoperatively compared to preoperative in TILMP Group and FSILMP group with p-value <0.05 S with more significant results in FSILMP group. One case developed a FTMH postoperatively in FSILMP group.Conclusion: Both techniques of vitrectomy with TILMP and FSILMP provided good anatomical and visual results in the surgical treatment of MTM with relatively better results in FSILMP group.